PSYCHOPHYSIOLOGICAL RESPONSES TO STRESS DURING HIGH-STAKES VOLLEYBALL MATCHES - Askar Tabynbaev (Modern American Journals, 2025)
This article explores the psychophysiological responses of volleyball players during high-stakes competitive matches. In sports like volleyball, where rapid decisions and intense physical effort are essential, stress responses can significantly impact performance. The study examines how psychological factors such as anxiety, emotional regulation, and cognitive focus interact with physiological indicators like heart rate, cortisol levels, and muscle tension under pressure. By analyzing contemporary research and applying findings to volleyball contexts, the article identifies key stress triggers, individual differences in response, and potential coping mechanisms. The ultimate goal is to provide evidence-based strategies for coaches, sports psychologists, and athletes to optimize performance through targeted psychological and physiological training.
Keywords: Volleyball, stress, psychophysiology, performance anxiety, heart rate variability, cortisol, sports psychology, elite athletes, coping strategies, high-pressure games